3D Nickel Scaffolded MoS2 Nanoflakes as Sodium Battery Anode with Improved Cycling Life and Rate Capability. Issue 2 (5th December 2018) - Zhu, Xiuting; Ren, Weina; Yang, Yaping; Cheng, Chuanwei
Abstract: We report the design and fabrication of 3D nickel inverse opals scaffolded MoS2 nanoflakes (MoS2 @Ni IO) by a combination of colloid spheres template, electrochemical deposition, and hydrothermal growth routes. The MoS2 @Ni IO is further evaluated as sodium ion battery anode, which exhibits a high specific capacity (696.9 mAh/g of the second cycle), long cycling life stability (620.1 mAh/g after 200 cycles at 200 mA/g) and excellent rate capability. The excellent electrochemical performance of the electrode can be attributed to the unique 3D electrode design, in which the 3D ordered Ni scaffold shortens the ion diffusion paths, improves the electronic conductivity and mechanical stability, while the ultrathin MoS2 nanoflakes are involving in the Na + insertion/extraction. Abstract : A novel 3D ordered Nickel scaffolded MoS2 nanoflakes electrode is designed for sodium ion batteries with improved cycling life and rate capability.